2004
DOI: 10.1093/humrep/deh101
|View full text |Cite
|
Sign up to set email alerts
|

Polscope analysis of meiotic spindle changes in living metaphase II human oocytes during the freezing and thawing procedures

Abstract: The current techniques of oocyte freezing and thawing inevitably cause meiotic spindle destruction. All spindles observed in thawed oocytes result from post-thaw reconstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
88
3
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(104 citation statements)
references
References 30 publications
10
88
3
2
Order By: Relevance
“…Since there are considerable apparent between-species and study differences, it was appropriate to examine the effect of vitrifying MII equine oocytes with or without their cumulus investment on post-warming meiotic spindle quality. And while post-warming spindle quality was generally poor in vitrified-warmed oocytes, despite a 6 h post-warming incubation to allow spindle reassembly and repair (Rienzi et al 2004), cumulus-enclosed oocytes fared significantly better than denuded oocytes (38 vs 3% normal spindles). In short, our results support the hypothesis that the cumulus helps to protect equine oocytes from damage during vitrification.…”
Section: Discussionmentioning
confidence: 98%
“…Since there are considerable apparent between-species and study differences, it was appropriate to examine the effect of vitrifying MII equine oocytes with or without their cumulus investment on post-warming meiotic spindle quality. And while post-warming spindle quality was generally poor in vitrified-warmed oocytes, despite a 6 h post-warming incubation to allow spindle reassembly and repair (Rienzi et al 2004), cumulus-enclosed oocytes fared significantly better than denuded oocytes (38 vs 3% normal spindles). In short, our results support the hypothesis that the cumulus helps to protect equine oocytes from damage during vitrification.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, although depolymerization of the oocyte's meiotic spindle is known to occur, a number of studies have now shown that the spindle reforms in the majority of oocytes after thawing [24][25][26][27][28][29]. The advent of ICSI for insemination has overcome any concern regarding potential premature cortical granule reaction [11].…”
Section: Introductionmentioning
confidence: 99%
“…Disruption of the meiotic spindle increases the risk of aneuploidy. These concerns were studied by Rienzi et al by slow freezing oocytes and looking at the meiotic spindle using computer-assisted polarization microscopy (Rienzi et al, 2004). This technique allowed visualization of the spindle in real time by evaluating living oocytes.…”
Section: Is Oocyte Cryopreservation "Experimental?"mentioning
confidence: 99%